Tourism Impact and Support for Future Development: Local’s Perspective at Ambaran Village / Suvidha Khanna and Sandeva Khajuria - Khanna, Suvidha; Khajuria, Sandeva (UiTM Press, 2016)
Ambaran is a small village in Jammu region of Jammu and Kashmir (J&K) State of India. Located on the bank of Chenab River, the village is inhabited by Dogra community of the region. Earlier, the village used to attract visitors from the surrounding at the times of religious events and congregation. Recently in the lastdecade, the Archeological Surveyof India excavatedcertainremains ofBuddhistdynasty dating back from 1st to 3rd century AD. This discovery has attracted the attention of the cultural and historica l societies and provides the scope of domestic tourism in the future. The village thus serves as a potentia l tourism destination and the future development of tourism is bound to some repercussions on the overall community. This study considers such impacts focuses on the perception of the local residents about impacts of future tourism development and their attitudinal support for future tourism development in the village. This study analyzes the tourism development impact, focusing on the demographic characteristics of the residents, their perception on tourism development and their future behavior respectively. Regression analysis, ANOVA, t-test are the major statistical techniques used in testing the study hypotheses.